2011
DOI: 10.5171/2011.228533
|View full text |Cite
|
Sign up to set email alerts
|

Employer Branding in Selected Companies in United Arab Emirates

Abstract: The article is an attempt to analyze the concept of employer branding and apply the concept to selected companies in United Arab Emirates (UAE). The concept of employer branding is drawn upon pre-existing theories, models, and practices across fields of marketing, human resource management and organizational behaviour. Various literature from marketing, organisational behaviour and human resource management were analysed to built the conceptual framework then three companies were selected to illustrate adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research on this extreme pattern indicated that one of the factors is negative stereotyping of US brands of automobiles by general US consumers (Ross, 2008). Further research revealed that ethnicity, country-of-origin or country image, and interpersonal influence might serve as drivers of automobile purchase and consumption phenomenon (Jawahitha, Nada and Haneen, 2011). Therefore, the consumer end of the brand equation is vital in building automotive brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on this extreme pattern indicated that one of the factors is negative stereotyping of US brands of automobiles by general US consumers (Ross, 2008). Further research revealed that ethnicity, country-of-origin or country image, and interpersonal influence might serve as drivers of automobile purchase and consumption phenomenon (Jawahitha, Nada and Haneen, 2011). Therefore, the consumer end of the brand equation is vital in building automotive brand.…”
Section: Literature Reviewmentioning
confidence: 99%